Evaluation of Guidelines for Assembly Instructions. Issue 12 (2016) - Mattsson, S.; Fast-Berglund, Å.; Li, D.
Abstract: In production industry assembly instructions are often in need of improvement. Today's instructions are often text based and are used only when learning the assembly. Due to a high product variety the instruction quality need to be perceptual in order for the operator to make fast and correct decisions. To educate and support personnel making instructions five guidelines that support operators' cognitive abilities have been developed. The guidelines were tested in three case studies with three different used groups: production technicians, students from higher vocational education and bachelor students. Results indicate that the theory behind the instructions is useful and valuable and that further development and testing is needed. The main thing both technicians and students learnt was to support the active cognitive processes, that instructions should be picture based and be as simple as possible.